User-centered technologies for blind children - Sánchez, Jaime (Human Technology, 2008)
The purpose of this paper is to review, summarize, and illustrate research work involving four audio-based games created within a user-centered design methodology through successive usability tasks and evaluations. These games were designed by considering the mental model of blind children and their styles of interaction to perceive and process data and information. The goal of these games was to enhance the cognitive development of spatial structures, memory, haptic perception, mathematical skills, navigation and orientation, and problem solving of blind children. Findings indicate significant improvements in learning and cognition from using audio-based tools specially tailored for the blind. That is, technologies for blind children, carefully tailored through user-centered design approaches, can make a significant contribution to cognitive development of these children. This paper contributes new insight into the design and implementation of audio-based virtual environments to facilitate learning and cognition in blind children.